Investigations on Ultrawideband Fractal Microstrip Patch Antenna Arrays for MIMO Wireless Communication Applications - Sohi, Arashpreet Kaur (My University, 2023)
Today, people around the globe are acknowledging the significance of wireless technology in their day-to-day activities such as entertainment, education, security and communication. With the tremendous development in the sector of mobile wireless technology (from the current 4G to the upcoming ultra-fast 5G standard), the demand for incorporating high speed, economical, wideband and low-powered ultra-wideband (UWB) antenna in modern wireless devices is increasing substantially. Moreover, the concept of multiple-input multiple-output (MIMO) antenna technology integrated in UWB systems helps to enhance signal-to-noise ratio (SNR) and data transmission speeds in a multipath propagation scenario. The research presented in this thesis addresses the four major constraints namely miniaturization, large bandwidth, high inter-element isolation and band-notch characteristics while modeling portable UWB-MIMO antennas for the advanced integrated systems. For developing small-sized UWB-MIMO antennas, the application of iteratively generated fractal geometries with the notable attributes of self-similarity and space-filling are employed in the antenna designs. The designed compact fractal antenna arrays are incorporated with defected ground structure (DGS), offset feeding, stub loading and slot etching approaches to excite a large band of operation. The decoupling networks, inter-element spacing and DGS geometries play a vital role to overcome the coupling issue between the neighboring radiators in a compact MIMO configuration. At last, to filter out the unwanted interference caused by the existing licensed applications in the operational UWB range, various notch structures are integrated in the array design. Objective 1 presents the modeling, simulation, and experimental analysis of six different dual port MIMO antenna arrays incorporated with different fractals (Sierpinski Gasket, Pythagorean tree, Circular, Koch curve, Koch Snowflake, and Koch Anti-Snowflake) and DGS geometries for UWB characteristics. The first design demonstrates an aperture-coupled Sierpinski gasket fractal (2nd order) MPA array combined with archimedean spiral-shaped and X-shaped DGSs to cover a UWB spectrum of 4.3-11.6 GHz with an acceptable inter-element isolation (S12/S21 ≤ -15.8 dB) and maximal gain of 4.7dBi (at 9.2GHz). In the second design, an aperture coupled MPA array with a 2nd iterative circular fractal and rectangular spiral-shaped DGSs to excite an operational band of 4.6-16.8 GHz with a maximal gain of 4.57dBi (at 6.6GHz) and a high port to-port isolation (S12/S21≤-19 dB) between the array elements. The third design illustrates an offset-fed aperture coupled, modified Pythagorean tree fractal (2nd order) antenna array iv integrated with hexagonal spiral-shaped DGS to cover a wide UWB range of 3.71-10.64GHz with a peak gain of 4.34dBi (at 9.4GHz) and a good degree of inter-port isolation (S12/S21≤- 16.1dB) characteristics. The fourth design presents a semi-circular MIMO antenna combined with 2nd iterative Koch-curve fractal and DGS approach to function in 4.395-10.184GHz (79.4% FBW)with a maximal gain of 3.84dBi (at 8.9GHz) and acceptable port-to-port isolation (S12/S21≤-16.1dB) response. In the fifth design, a circular MIMO antenna integrated with a modified Koch-Snowflake fractal (4th iteration), offset-feeding, and DGS technique is designed to operate in a 3.3-18GHz spectrum with a considerable level of isolation (S21/S12≤-16dB) and peak gain of 5.39dBi (at 13.5GHz). In the last design, a compact microstrip-fed Koch Anti snowflake fractal MIMO antenna integrated with the DGS technique is designed to successfully cover a large frequency band from 2.48-15.42 GHz (144.6% FBW) with a peak gain of 5.16dBi (at 7.48 GHz) and significant degree of isolation (S21/S12≤ -17dB) between the antenna ports. Therefore, the applicability of the above-mentioned antenna arrays to operate in portable UWB communication devices is supported by their compact dimensions, large operational band, high gain, good inter-element isolation, and excellent diversity performance characteristics. In objective 2, the previously designed two-port Sierpinski gasket and Koch snowflake fractal MIMO antennas (in objective 1) are configured to four-port networks with some modifications in the ground geometry for improved operational bandwidth, port-to-port isolation, and diversity operation characteristics. The first design reports a quad-port, aperture-coupled Sierpinski gasket fractal (iterated to 2nd order) antenna, incorporated with spiral-shaped DGS and offset-feeding approach to effectively resonate in the 3.07-11GHz range. An optimum isolation response between the antenna ports is realized by carefully selecting the center-to center spacing between the antenna elements and truncating an X-shaped slot from the center of the ground. In the second design, a microstrip-fed, quad-port Koch Snowflake fractal (4th iteration order) MIMO antenna is integrated with the DGSs and feedline modifications (tapering and offsetting) to convert the multi-resonant response generated by fractal geometry into the desired UWB spectrum (3.1-18GHz). A considerable isolation behavior is accomplished by carefully optimizing the separation distance between the array elements and incorporating the decoupling network (vertical ground stubs and semi-circular rings) in the common ground plane. Objective 3 proposes band-notch functionality in the previously designed two dual-port and two quad-port fractal UWB-MIMO antennas in objective 1 and objective 2 respectively. In the v first design, the dual-port Pythagorean tree fractal (2nd iteration) UWB antenna successfully rejects the three interfering ranges (downlink C-band: 3.81-4.16GHz, WLAN: 5.22-5.84GHz, X-band: 7.84-8.44GHz) coherent in the functional UWB range by incorporating two L-shaped slits, a U-shaped slot, and an SRR pair respectively in each feedline of the proposed array. In the second design, a dual-port modified Koch anti-snowflake fractal (iterated up to 3rd order) UWB antenna is designed for filtering six interfering narrow bands (WiMAX (3.3-3.78 GHz), INSAT (reception: 4.52-4.9GHz), WLAN (5.16-5.84GHz), super-extended C-band (6.3- 6.93GHz), ITU-8 (7.63-8.62GHz) and amateur radio (9.96-10.52GHz)) the excited operational band (2.48-15.42 GHz) by integrating a Z-shaped slit (patch), inverted L-shaped slit (patch), pair of L-shaped slits (reduced ground plane), two rectangular SRR pairs (feedline) and G shaped slot (feedline) in the array design. In the third design, a quad-port aperture-coupled Sierpinski gasket fractal (iterated to 2nd order) antenna effectively eliminates the interference caused by C-band (at 4.01GHz), WLAN (at 5.56GHz), and radio-location (at 8.8GHz) band in the working UWB range by incorporating three distinct notch structures (circular SRRs, U shaped slot, and rectangular SRRs) into each feedline of the array geometry. In the fourth design, a four-element Koch Snowflake fractal (4th iteration order) UWB array effectively suppresses the interfering C-band (downlink satellite: 4.01GHz), WLAN (at 5.56GHz), (uplink satellite: 6.882GHz), and ITU-8 (at 8.18GHz) from the functional UWB range by loading a modified Z-shaped slot (patch), rectangular SRR pair (reduced ground), rectangular SRR (patch) and U-shaped slot (feedline) in the array design. All the above-reported array designs exhibit admissible values of MIMO metrics like ECC, DG, MEG, CCL, and TARC that justify the application of the proposed arrays in UWB communication systems
Doctoral Thesis
Keywords: Fractal MSA; MIMO Antenna Arrays; Split Ring Resonators; Band Notch